2007
DOI: 10.1111/j.1365-2699.2007.01762.x
|View full text |Cite
|
Sign up to set email alerts
|

Divergent echolocation call frequencies in insular rhinolophids (Chiroptera): a case of character displacement?

Abstract: Lo studio dimostra l'esistenza di fenomeni di divergenza bioacustica in popolazioni simpatriche insulari di chirotteri rinolofidi collegandoli a un possibile processo di character displacement generato dalla necessità di mantenere bande separate di comunicazione tra specie divers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
82
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 49 publications
3
82
0
1
Order By: Relevance
“…Geographic variation in social call structure has been observed in a number of species (e.g., Russo and Jones, 1999;Pfalzer and Kusch, 2003;Russo et al 2007Russo et al , 2009. Differences in call structure may be due to genetic factors (Russo et al, 2009), social learning (Esser and Schmidt, 1989;Boughman, 1998), or environmental conditions such as temperature (Jones and Ransome, 1993) or habitat structure (Russo and Jones, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geographic variation in social call structure has been observed in a number of species (e.g., Russo and Jones, 1999;Pfalzer and Kusch, 2003;Russo et al 2007Russo et al , 2009. Differences in call structure may be due to genetic factors (Russo et al, 2009), social learning (Esser and Schmidt, 1989;Boughman, 1998), or environmental conditions such as temperature (Jones and Ransome, 1993) or habitat structure (Russo and Jones, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Because echo location calls can be intercepted by other bats, they also can serve a communication function, as in the case of eavesdropping (e.g., Barclay, 1982;Balcombe and Fenton, 1988;Gillam, 2007). Further, differences in echolocation call structure may play an important role in species recognition (Russo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The results suggested that greater horseshoe bats may use individually distinct, "private" call frequencies for intra-individual communication and recognition. Studies have documented that a "private bandwidth of frequency" may have crucial functions in social communication and sexual behavior, for example, allowing bats to recognize relative individuals or attract copulation partners of right species [34]. In mating season, the male greater horseshoe bats have a polygynous mating system and male territoriality [35].…”
Section: Discussionmentioning
confidence: 99%
“…hunting and roosting) and refer to the former as 'social information'. Vocal signatures in bat echolocation calls can encode information ranging from species identity [18,19], age [20,21] and sex [22,23] to group affiliation [21,24] and individual identity [25][26][27] of the calling bat. However, it is still controversial as to what extent this social information is actually exploited by eavesdropping conspecifics [11,17,28,29].…”
Section: Introductionmentioning
confidence: 99%